The landscape of basic gene therapy approaches in inherited retinal dystrophies - Xia, Jianhua; Gu, Lei; Pan, Qing (Frontiers in Ophthalmology, 2023)
The study of gene therapies has been of particular interest in recent decades due to their promising potential to slow or even rescue the degeneration of the retina in inherited retinal dystrophies (IRDs). Here, we review the current approaches to gene therapy trials on IRDs, including the selection of animal models, therapeutic window, vectors and dosages. Mice are typically the first choice of animal models and recombinant adeno-associated virus (rAAV) of serotype 8 is the most common vector for loss-of-function IRDs. Furthermore, the therapeutic window should be considered to ensure efficacy before retinal degeneration occurs if possible, and dosages must be tailored to each approach.